IGR J19294+1816: a new Be-X-ray binary revealed through infrared spectroscopy. Issue 2 (9th February 2018) - Rodes-Roca, J J; Bernabeu, G; Magazzù, A; Torrejón, J M; Solano, E
Abstract: The aim of this work is to characterize the counterpart to the INTErnational Gamma-Ray Astrophysics Laboratory high-mass X-ray binary candidate IGR J19294+1816 so as to establish its true nature. We obtained H -band spectra of the selected counterpart acquired with the Near Infrared Camera and Spectrograph instrument mounted on the Telescopio Nazionale Galileo 3.5-m telescope which represents the first infrared spectrum ever taken of this source. We complement the spectral analysis with infrared photometry from UKIDSS, 2MASS, WISE, and NEOWISE data bases. We classify the mass donor as a Be star. Subsequently, we compute its distance by properly taking into account the contamination produced by the circumstellar envelope. The findings indicate that IGR J19294+1816 is a transient source with a B1Ve donor at a distance of d  = 11 ± 1 kpc, and luminosities of the order of 10 36–37  erg s −1, displaying the typical behaviour of a Be-X-ray binary.